Überblick über das Steuerrecht in der Bundesrepublik Deutschland - Rackebrandt, Traute (Univerzita Pardubice, 2001)
The contribution deals with a survay of legal tax frame in Germany. There are explained the main conception and terms and there is demonstrated the tax calculation on some example.
Keywords: Německo; daňová reforma; daňové právo